2011
DOI: 10.1055/s-0030-1256222
|View full text |Cite
|
Sign up to set email alerts
|

Ökonomische Bewertung ambulanter Arztkontakte von COPD-Patienten in Deutschland

Abstract: Despite its low level of evidence, the use of expert opinion can serve as a valuable and legitimate tool; especially when the literature does not provide any or only outdated information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A systematic review [18] of 7 COPD studies in Germany found annual costs per COPD patient between €1212 and €3492 (price year 2010) from a societal perspective. Most studies are limited to singular direct [4, 19, 20] or indirect [21] cost categories. Only three [2224] studies estimated direct and indirect costs, which were restricted to mean annual costs per COPD patient and did not report stratified costs for GOLD grades.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [18] of 7 COPD studies in Germany found annual costs per COPD patient between €1212 and €3492 (price year 2010) from a societal perspective. Most studies are limited to singular direct [4, 19, 20] or indirect [21] cost categories. Only three [2224] studies estimated direct and indirect costs, which were restricted to mean annual costs per COPD patient and did not report stratified costs for GOLD grades.…”
Section: Discussionmentioning
confidence: 99%